Comparison of jump height values derived from a force platform and vertec - VanderZanden, T.; Wurm, B.; Hopkins, W. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study simultaneously assessed jump heights derived from a force platform and a Vertec as well as the reliability of each instrument. Twenty-one recreationally active adults performed 3 maximal countermovement jumps reaching to a Vertec that was placed above the force platform. A repeated measures ANOVA was used to assess differences between Vertec jump height and force platform derived jump height. Results revealed a 27% higher jump height when assessed by the Vertec, compared to the force platform. Intra-class correlations were used to assess trial-to-trial reliability. Both instruments displayed excellent reliability. Practitioners could use the following regression equation to interpret measurements from the force platform: Vertec jump height = force platform height (1.024) + 0.142m.